2019
DOI: 10.3390/app9050931
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Feature Comparison Study of Open-Source Container Orchestration Frameworks

Abstract: (1) Background: Container orchestration frameworks provide support for management ofcomplex distributed applications. Different frameworks have emerged only recently, and they havebeen in constant evolution as new features are being introduced. This reality makes it difficult forpractitioners and researchers to maintain a clear view of the technology space. (2) Methods: wepresent a descriptive feature comparison study of the three most prominent orchestrationframeworks: Docker Swarm, Kubernetes, and Mesos, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 44 publications
0
27
0
3
Order By: Relevance
“…For Kubernetes v1.13 -the default k8s release of the major cloud providers at the time of our research -we identified 162 features in total. The small number of 14 additional features is in line with the emerging trend that the number of feature additions has significantly decreased in all mainstream orchestration platforms [19]. This trend can be explained by the fact that k8s already appeared as a de-facto standard [21]- [23] and the opensource development efforts refocused on improving the security, performance and robustness of existing k8s features [24]- [26].…”
Section: Container Orchestration Feature Taxonomymentioning
confidence: 76%
See 4 more Smart Citations
“…For Kubernetes v1.13 -the default k8s release of the major cloud providers at the time of our research -we identified 162 features in total. The small number of 14 additional features is in line with the emerging trend that the number of feature additions has significantly decreased in all mainstream orchestration platforms [19]. This trend can be explained by the fact that k8s already appeared as a de-facto standard [21]- [23] and the opensource development efforts refocused on improving the security, performance and robustness of existing k8s features [24]- [26].…”
Section: Container Orchestration Feature Taxonomymentioning
confidence: 76%
“…For the first concern, we have already conducted a comprehensive study of the documentation of existing opensource container orchestration platforms, including Docker Swarm, Mesos and Kubernetes [19]. In this study, we have distinguished between common features (shared by at least two orchestration platforms) and 54 unique features.…”
Section: Container Orchestration Feature Taxonomymentioning
confidence: 99%
See 3 more Smart Citations